The Warmth of Other Suns - Wilkerson, Isabel (UK Penguin Books, 2010)
Brought to you by Penguin. From the winner of the Pulitzer Prize, this is one of the great untold stories of American history: the migration of black citizens who fled the south and went north in search of a better life From 1915 to 1970, an exodus of almost six million people would change the face of America. With stunning historical detail, Pulitzer prize-winning journalist Isabel Wilkerson gives us this definitive, vividly dramatic account of how these journeys unfolded.
Include Index
Keywords: Sociology Reference -- Black & African American History